Screening for potential Striga hermonthica fungal and bacterial biocontrol agents from suppressive soils in Western Kenya - Neondo, J.O.; Alakonya, A.E.; Kasili, R.W. (2017)
Striga hermonthica is a hemiparasitic weed that causes huge grain yield losses to small-scale farmers in Africa. Effective biocontrol agents against S. hermonthica can sustainably mitigate these losses. This study characterized the biocontrol potential of culturable fungal and bacterial isolates from S. hermonthica suppressive soils of western Kenya. These isolates were screened for their ability to produce antibiotic compounds and extra cellular enzymes and also their ability to cause S. hermonthica seed decay. Genomic DNA of the selected bacterial and fungal isolates was extracted and partial characterization of 16S rRNA and 18S rRNA genes performed respectively. Analysis show that antibiosis and enzymatic properties of potential biocontrol isolates correlated positively. Isolate KY041696 recorded high antibiosis, enzymatic and seed decay values. This study also revealed that bioactive bacterial isolates belonged to Bacillus, Streptomyces and Rhizobium genera. In this study, no fungal isolate caused S. hermonthica seed decay. This study therefore provides baseline information on the potential biocontrol microbes against S. hermonthica in Western Kenya that could be exploited further in the management of the weed.